2021
DOI: 10.1155/2021/1767308
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Prediction Model of Hot Metal Silicon Content Based on Improved GA‐BPNN

Abstract: The inconsistency of the detection period of blast furnace data and the large time delay of key parameters make the prediction of the hot metal silicon content face huge challenges. Aiming at the problem that the hot metal silicon content is not consistent with the detection period of time series of multiple control parameters, the cubic spline interpolation fitting model was used to realize the data integration of multiple detection periods. The large time delay of the blast furnace iron making process was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Similarly, Cui et al utilized GA to optimize the parameters of the BP neural network model, enhancing the convergence speed and achieving global optimization. The results showed that the GA-BPNN improved the prediction accuracy of BPNN, with an average absolute error of 0.05009, for predicting the silicon content of iron in actual production [23]. Despite existing studies that have investigated the combination of genetic algorithms (GA) with BPNN, little research has focused on GA-based optimization of BPNN specifically for moisture content (M C ) prediction in green tea processing.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Cui et al utilized GA to optimize the parameters of the BP neural network model, enhancing the convergence speed and achieving global optimization. The results showed that the GA-BPNN improved the prediction accuracy of BPNN, with an average absolute error of 0.05009, for predicting the silicon content of iron in actual production [23]. Despite existing studies that have investigated the combination of genetic algorithms (GA) with BPNN, little research has focused on GA-based optimization of BPNN specifically for moisture content (M C ) prediction in green tea processing.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%